Induced Foxp3+ T Cells Colonizing Tolerated Allografts Exhibit the Hypomethylation Pattern Typical of Mature Regulatory T Cells - Hilbrands, Robert; Chen, Ye; Kendal, Adrian R.; Adams, Elizabeth; Cobbold, Stephen P.; Waldmann, Herman; Howie, Duncan (Frontiers in Immunology, 2016)
Regulatory T cells expressing the transcription factor Foxp3 require acquisition of a specific hypomethylation pattern to ensure optimal functional commitment, limited lineage plasticity and long-term maintenance of tolerance. A better understanding of the molecular mechanisms involved in the generation of these epigenetic changes in vivo will contribute to the clinical exploitation of Foxp3+Treg. Here we show that both in vitro and in vivo generated antigen specific Foxp3+Treg can acquire Treg-specific epigenetic characteristics and prevent skin graft rejection in an animal model.